Preliminary Study of Strategies for Developing Tourism Destinations - Bahri, Efri Syamsul (International Journal of Strategic Studies, 2024)
Tourism Destinations in Indonesia are experiencing rapid development. This study aims to explain the strategy for developing tourism destinations. This study uses a qualitative method with a descriptive approach. In addition, this research also uses a literature study approach. Research reference data were obtained from journals and reference books related to tourism development strategies. The study results found eight strategies for developing tourism destinations: optimizing environmental management, optimizing potential and community assistance, managing intangible cultural assets, managing tangible cultural assets, fostering surrounding communities, improving product quality, and organizing integrated tourism activities. The government and tourism destination development stakeholders need to respond to the results of this research by optimizing the strategies identified in this study.